A qualitative analysis on occupational health and safety conditions at small construction projects in the Brazilian construction sector - Gomes, H. P. (2016)
The main objective of this study is to analyze the perception of Occupational Health and Safety in small construction projects in the Brazilian construction industry. The adopted approach is qualitative in nature and seeks to understand the character of the current practices through interviews held with ‘actors’ who are directly involved in small-scale building sites, as well as with others who are involved in large-scale work sites. In Brazil, there is a weakness in supervision at small construction projects. This is due to numerous factors, such as the low visibility of these types of works and short deadlines, as well as the lack of knowledge about Occupational Health and Safety. This study reinforces and illustrates the idea of the inherent dangers involved in the occupational health of workers in small construction projects. It also indicates that there is a need to put greater emphasis on compliance with Occupational Health and Safety principles, which are covered by the current Brazilian Legislation and Regulatory Standards. This should be undertaken in order to ensure that the work in small-scale building sites is more visible and, especially, to ensure acceptable health and safety conditions for construction workers.